Perlindungan Dan Pengelolaan Cagar Budaya Situs Banten Girang Berdasarkan UndangUndang Cagar Budaya - Khoirunnisa, Salsabila (Beleid, 2024)
ABSTRACTThis research examines the management and role of the Cultural Heritage Protection Center (BPCB) in preserving cultural heritage at the Banten Girang Site. Cultural heritage is a valuable legacy that needs to be safeguarded and preserved for the enjoyment of present and future generations. BPCB has the primary responsibility for managing and protecting cultural heritage, including the significant historical and cultural value of the Banten Girang Site. The aim of this study is to analyze the approaches and strategies employed by BPCB in managing and protecting the Banten Girang Site. The research methods used include document analysis, interviews with relevant stakeholders, and a literature review on cultural heritage management. The findings of the study indicate that BPCB has implemented various efforts to ensure effective protection of the Banten Girang Site. The role of BPCB in the protection of the Banten Girang cultural heritage site includes monitoring, control, and surveillance of activities that could potentially damage the site. Additionally, BPCB conducts socialization and education to raise awareness among the community about the importance of preserving cultural heritage. This research provides a better understanding of the management and role of BPCB in the protection of the Banten Girang cultural heritage site. These findings can serve as a basis for enhancing strategies and policies in safeguarding cultural heritage in the future.Keyword: Banten Girang Site, BPCB, Cultural Heritage, Management. ABSTRAKPenelitian ini mengkaji pengelolaan dan peran Balai Perlindungan Cagar Budaya (BPCB) dalam melindungi cagar budaya di Situs Banten Girang. Cagar budaya merupakan warisan berharga yang perlu dijaga dan dilestarikan agar dapat dinikmati oleh generasi sekarang dan mendatang. BPCB memiliki tanggung jawab utama dalam pengelolaan dan perlindungan cagar budaya, termasuk Situs Banten Girang yang memiliki nilai sejarah dan budaya yang signifikan. Penelitian ini bertujuan untuk menganalisis pendekatan dan strategi yang dilakukan oleh BPCB dalam mengelola dan melindungi Situs Banten Girang. Metode penelitian yang digunakan meliputi analisis dokumen, wawancara dengan pihak terkait, dan studi literatur terkait pengelolaan cagar budaya. Hasil penelitian menunjukkan bahwa BPCB telah melaksanakan berbagai upaya untuk memastikan perlindungan yang efektif terhadap Situs Banten Girang. Peran BPCB dalam perlindungan cagar budaya Situs Banten Girang meliputi pengawasan, pengendalian, dan pemantauan terhadap kegiatan yang berpotensi merusak situs tersebut. Selain itu, BPCB juga melakukan sosialisasi dan edukasi kepada masyarakat mengenai pentingnya pelestarian cagar budaya. Penelitian ini memberikan pemahaman yang lebih baik tentang pengelolaan dan peran BPCB dalam perlindungan cagar budaya Situs Banten Girang. Temuan ini dapat menjadi dasar untuk meningkatkan strategi dan kebijakan dalam melindungi cagar budaya di masa depan.Kata Kunci: : Situs Banten Girang, BPCB, Cagar Budaya, Pengelolaan.